A Study on Level of Awareness of Inclusive Education in Elementary Education: A Comparative Study with Special Reference to Jagun, Tinsukia District of Assam - Dutta, Barasha; Sinha, Sandip (Integrated Journal for Research in Arts and Humanities, 2024)
The present study allows the researcher to understand whether government and private elementary schools are differed on the status, basic infrastructural facilities, teaching strategies, organizing co-curricular activities, availability of resources on the basis of the inclusive education. The prime objective of the study is to compare the level of awareness of inclusive education among teachers in private and government elementary schools in Jagun, Tinsukia District of Assam. A descriptive survey method aided by a self-developed questionnaire was used to collect data. The population of the study comprises teachers from both private and government funded elementary schools from Jagun. To fulfill the target a total of eight schools were randomly selected from where eighty teachers from both private and government schools provided with their opinions. Findings of the study suggested that children especially CWSN needs extra care and facilities according to their needs provided and facilitated with some acts and policies for CWSN which must be implemented in the both public and private funded institutes. Furthermore the NEP-2020 laid stress on inclusive-education to promote education towards holistic growth and development.